PERTUMBUHAN EKONOMI DAN KETIMPANGAN WILAYAH DI PROVINSI RIAU - Sisca Vaulina; Limetry Liana (UIR Press, 2015)
The purpose this research is to higlight the economic growth and the inequality level acrross regions in Riau province. This research used case method and time series data for 2010-2014. The data were analyzed using economic growth from Typology Klassen, Williamson inequality index, and Theil Entropy Index. The results showed that based on the typology Klassen, the economic growth in Riau Province is located in Quadrant I. This means that Riau Province is a province which is included in the group of advanced and fast growing region. Based on Williamson index, Riau Province from the year 2010-2014 had inequality with a range of 0.727 to 0.960 and high inequality criterion or the average index of inequality was 0,862. Although the criteria were high inequality, the index value decreased during the analysis. Based on Enthropi Theil index, the index value was an average of 0.204. During the period 2010-2014, the declining trend of the index value was seemed at the beginning in 2013. The decreasing inequality was caused by the concentration of economic activtities in certain region, equitable allocation of investment, and mobility of production factors between regions.